Sharp power and the future of conflict - Ng, Kian Shin (Nanyang Technological University, 2021)
A state’s employ of foreign policy often revolves around two types of power to shape the behaviour of other states. Hard power involves the use of physical force to force other states to change their behaviour. Soft power on the other hand, utilises the mechanism of attraction, to persuade other states in changing their behaviour. However, advances in communication technologies allows states to employ new tactics involving the manipulation of information. This thesis expands on the concept known as sharp power and analyses two case studies that employed disinformation to deceive and interfere with the domestic politics of the target state to fulfil their own foreign policy objectives. The paper investigates why states engage in sharp power and the factors that contribute to its success.